Transient negative biochar effects on plant growth are strongest after microbial species loss. (December 2017) - Hol, W.H. Gera; Vestergård, Mette; ten Hooven, Freddy; Duyts, Henk; van de Voorde, Tess F.J.; Bezemer, T. Martijn
Abstract: Biochar has been explored as an organic amendment to improve soil quality and benefit plant growth. The overall positive effects of biochar on crop yields are generally attributed to abiotic changes, while the alternative causal pathway via changes in soil biota is unexplored. We compared plant growth effects of legumes in sterile soil inoculated with dilutions of soil and soil microbial suspensions to determine the direct effects of biochar-induced changes in soil biota on plant growth. Suspensions and soil were from soil amended with biochar and soil without biochar. By comparing consecutive plant growth phases on the same inoculated soils, we also determined the temporal effects of soil biota from biochar-amended and control soils. Biota from biochar-amended soil was less beneficial for Medicago sativa growth, especially with small amounts of inocula. Flowering was delayed in the presence of biota from biochar plots. Inoculum with either soil or soil suspension gave similar results for plant biomass, indicating that microorganisms play a major role. Vicia villosa growth did not respond to the various inocula, even though the inoculum quantity strongly affected nematode community composition and protozoan abundance. In a later growing phase the negative effect of biochar-associated biota on Medicago growth mostly disappeared, which leads to the conclusion that the benefits of biochar application via abiotic changes may outweigh the negative effects of biochar on soil biota. Highlights: Biota from biochar-amended soil are less beneficial for legume plant growth. Flowering was delayed in the presence of biota from biochar plots. Inoculum with soil or soil suspension gave similar results to each other. Inoculum quantity determines nematode community composition and protozoan abundance. Increasing inoculum reduced positive feedback.